Outcome of extracorporeal shock wave lithotripsy for renal and upper ureteric stone clearance (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Extracorporeal shockwave lithotripsy (ESWL) is a day care, less invasive procedure not requiring anesthesia for the treatment of renal and ureteric stones. Method: This was a cross sectional study of retrospectively collected data on ESWL during May 2018 to January 2020 at the department of Urology, Bir Hospital, National Academy of Medical Sciences (NAMS), Nepal. The data on ESWL for renal and upper ureteric stone up to the size of 20 mm were included. Stone clearance was defined as stone fragment